GROUND IMPROVEMENT AND DESIGN OF LOWER STRUCTURE OF THE GRID: GEDEBAGE MILLENIAL RESIDENTIAL PROJECT - Santoso, Bryant
Geotechnical design is very critical and is needed as a support system for the structure above. This final project has the aim to improve the soil bearing capacity before starting the construction process so that the design of other geotechnical elements is more optimal. In addition, the foundation will also be designed that can withstand the burden of the upper building structure and a permanent retaining wall system to overcome soil landslides due to differences in elevation between the basement and on the outside of the building. Ground improvement is carried out by using the PVD method which aims to accelerate the consolidation process and the fill preloading to increase the bearing capacity of the soil. This improvement is needed to accommodate soft soil which is up to a depth of 30 m. From the improvement, obtained the addition of bearing capacity of 12.19 kPa. The duration of the ground improvement requires 157 days starting from the construction of the preloading fill stage 1 to waiting for the soil to reach a consolidation degree of 90% The foundation design uses a bore pile foundation with a diameter of 1.2 meters with a depth of 40 meters that is adjusted to the characteristics of the soil. Analysis includes the Axial and Lateral bearing capacity of the foundation and settlement of the foundation. Calculation of axial bearing capacity and the settlement is done manually, while the calculation of lateral bearing capacity is calculated by LPILE software. The analysis of the pile group foundation is calculated by GROUP software. Reinforcement of the pile cap is calculated using ETABS software to get the ultimate forces. Design of retaining wall as a permanent structure with a depth of 35 meters and a thickness of 1 m was built to accommodate the basement excavation as deep as 3.5 meters. The diaphragm wall uses temporary reinforcement/anchors such as H400 steel and Counterweight soil as a opposite force to provide balance and the stability of the excavation. Modelling and analysis is carried out with PLAXIS 2D software to get the safety factors, deflection, and ultimate force that works on the wall. The results of the design are submitted in detailed planning documents, dimensions, and detailed images of the design.